GAMBARAN KADAR ASAM URAT WANITA MENOPAUSE YANG MENGKONSUMSI AIR PUTIH 2 LITER/HARI - Pratiwi Irawan, Mega; Devitria, Rosa; Maulana, Ervita Ika; Atthahirah, Luthfiah (Ensiklopedia of Journal, 2025)
Uric acid is the end product of purine metabolism that occurs in the body. Increased uric acid levels are more common in men, while in women, uric acid levels tend to be normal and will increase after entering menopause. This is because women have more estrogen, which is uricosuric, which triggers the excretion of more uric acid through urine. Uric acid levels can be lowered by consuming water because water can dilute and dissolve uric acid, making it easier for the kidneys to excrete uric acid from the body through urine. This study aims to determine the uric acid levels of postmenopausal women who consume 2 liters of water per day. This research uses cross sectional method. In this study, 23 menopausal women respondents in RT.001 Simpang Fixed Darul Ichsan Village were asked to consume 2 liters of water/day for 2 weeks. The results showed that the average uric acid level before consuming 2 liters of water/day was 6.587 ± 0.3266 mg/dL, while after consuming 2 liters of water it was 5.013 ± 0.7594 mg/dL. The results of the dependent t test were found to be significant, namely P value 0.000 0.05. This shows that there is a significant difference in uric acid levels in postmenopausal women before and after consuming 2 liters of water/day. From the research that has been done, it can be concluded that there is a significant difference between uric acid levels in menopausal women before and after consuming 2 liters of water/day.Keywords: Uric Acid, Menopause, Water